High-quality draft genome and characterization of commercially potent probiotic strains - Ayesha Sulthana; Suvarna G. Lakshmi; Ratna Sudha Madempudi (Genomics & Informatics)
Lactobacillus acidophilus UBLA-34, L. paracasei UBLPC-35, L. plantarum UBLP-40, and L. reuteri UBLRU-87 were isolated from different varieties of fermented foods. To determine the probiotic safety at the strain level, the whole genome of the respective strains was sequenced, assembled, and characterized. Both the core-genome and pan-genome phylogeny showed that L. reuteri was closest to L. plantarum than to L. acidophilus, which was closest to L. paracasei. The genomic analysis of all the strains confirmed the absence of genes encoding putative virulence factors, antibiotic resistance, and the plasmids.